Increased Circulating and Urinary Levels of Soluble TAM Receptors in Diabetic Nephropathy - Ochodnicky, Peter; Lattenist, Lionel; Ahdi, Mohamed; Kers, Jesper; Uil, Melissa; Claessen, Nike; Leemans, Jaklien C; Florquin, Sandrine; Meijers, Joost C M; Gerdes, Victor E A; Roelofs, Joris J T H (The American journal of pathology, 2017)
TAM receptors (Tyro3, Axl, and Mer) have been implicated in innate immunity. Circulating TAM receptor soluble forms (sTyro3, sAxl, sMer) are related to autoimmune disorders. We investigated TAM and their ligand protein S in patients with diabetes. Urinary and plasma levels of protein S, sTyro3, sAxl, and sMer were determined in 126 patients with diabetes assigned to a normoalbuminuric or macroalbuminuric (urinary albumin excretion <30 mg/24 hours and >300 mg/24 hours, respectively) study group and 18 healthy volunteers. TAM and protein S immunostaining was performed on kidney biopsy specimens from patients with diabetic nephropathy (n = 9) and controls (n = 6). TAM expression and shedding by tubular epithelial cells were investigated by PCR and enzyme-linked immunosorbent assay in an in vitro diabetes model. Patients with macroalbuminuria diabetes had higher circulating levels of sMer and more urinary sTyro3 and sMer than normoalbuminuric diabetics. Increased clearance of sTyro3 and sMer was associated with loss of tubular Tyro3 and Mer expression in diabetic nephropathy tissue and glomerular depositions of protein S. During in vitro diabetes, human kidney cells had down-regulation of Tyro3 and Mer mRNA and increased shedding of sTyro3 and sMer. Renal injury in diabetes is associated with elevated systemic and urine levels of sMer and sTyro3. This is the first study reporting excretion of sTAM receptors in urine, identifying the kidney as a source of sTAM.